(untitled) (Purbanchal University Health Journal, 2025)
Introduction: Hospitalization, itself is an anxiety provoking situation whatever may be the problem. Surgery being an invasive and traumatic procedure, triggers physiological, cognitive and behavioral responses among patients resulting in anxiety. It affects about one in two patients having surgery in low- and middle-income countries (LMICs) resulting in delayed recovery. Objective: The study aims to assess the preoperative anxiety among patients undergoing surgery in a tertiary hospital of Morang district. Method: A cross-sectional descriptive research design was used with face-to-face interview using standard APAIS (Amsterdam Preoperative Anxiety and Information Scale) to assess presence of anxiety before surgery. The study population was patients admitted in surgery, gynecology, ENT & orthopedic wards for the surgery. Data was collected after ethical clearance from the Nepal Health Research Council. Descriptive statistics as mean, frequency and standard deviation were used to assess prevalence of pre-operative anxiety among patients. Result: About half (40.9%) of the respondents were of age group 20-40 years, 62.9% were male and almost all were Hindu by religion. More than three-fourth were married whereas less than one-third were illiterate and unemployed. Among the participants, more than one-fourth did not know the type of surgery they were undergoing and the type of anesthesia being used during the surgery. More than three-forth (77.3%) were informed about their diagnosis whereas only 29.5% were informed about possible complications of the surgery. Findings showed that 37.1% patients had anxiety related to surgery. Conclusion: More than one-third of the patients undergoing elective surgery had anxiety related to surgery. More than half of the patients undergoing surgery had not received adequate pre-operative information related to type of surgery and type of anesthesia being used. It is imperative to appropriately assess and address pre-operative anxiety with timely visit by anesthesiologist, premedication with anxiolytic medicines and psychological preparation of the patient.